2013
DOI: 10.1159/000347060
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Deficiency in Dendritic Cells Enhances the Adjuvant Effect of Ambient Ultrafine Particles on Allergic Sensitization

Abstract: Particulate matter (PM) is an important risk factor for asthma. Generation of oxidative stress by PM is a major mechanism of its health effects. Transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) mediates antioxidant and phase II enzymes and is essential in protecting against oxidative stress and lung inflammation. We have previously shown that ambient ultrafine particles (UFP) could exert a potent adjuvant effect on allergic sensitization to ovalbumin (OVA) in mice. We hypothesized that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Because inflammatory effects of PM have been attributed to oxidative stress (Li et al 2008; 2009; 2013), protein expression of HO-1 in lung tissue was determined. Epithelial cells, fibroblasts, and macrophages were positive for HO-1 expression (Figure 5, A-D), especially following OVA/OVA and OVA+PM/OVA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Because inflammatory effects of PM have been attributed to oxidative stress (Li et al 2008; 2009; 2013), protein expression of HO-1 in lung tissue was determined. Epithelial cells, fibroblasts, and macrophages were positive for HO-1 expression (Figure 5, A-D), especially following OVA/OVA and OVA+PM/OVA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Further, evidence from in vivo studies utilizing chronic UF ambient particle exposure demonstrated activation of the Nrf-2 signaling pathway, a regulator of HO-1 and a pathway subject to diminished upregulation with aging that might potentially explain additional susceptibility in the aging population to PM pollution (Zhang et al, 2012). To this point, Li et al (2013) recently demonstrated that adoptive transfer of dendritic cells exposed to UF particles with allergen resulted in a more severe allergic response in Nrf-2 −/-dendritic cells than for Nrf-2 +/+ . Taken together with the findings from this study, the data suggest that further research into Nrf-2 mediated HO-1 activity and induction may be critical to understanding the ability of particles to worsen allergic airway inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…While this does not preclude Nrf2 from having a role during sensitization, these data indicate that Nrf2-mediated reduction in asthma occurs at the challenge phase, which may be due to acute cytoprotective responses. Other studies demonstrate that Nrf2 alters dendritic cell function and skews the Th2 response (29,57), suggesting that Nrf2 may also function during sensitization. We explored the role of Nrf2 in airway epithelial cell function, which is an important component of asthma susceptibility, and we showed that Nrf2 has a strong protective role in the airway epithelium of sensitized and challenged mice.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, dendritic cells from Nrf2-deficient mice display enhanced surface expression of activation markers, increased oxidative stress, and heightened Th2 responses, compared with dendritic cells from wild-type mice after ex vivo stimulation with allergen (29,40,57). Furthermore, Nrf2 protein levels and Nrf2-regulated antioxidant responses are markedly reduced in airway smooth muscle cells from severe asthmatic subjects, compared with normal subjects, suggesting that the Nrf2 response may be impaired in asthmatic subjects (32).…”
mentioning
confidence: 98%